Task-Based Language Teaching: Understanding of The Task - Nofrina Eka Putri; Sukma Yudistira; Carbiriena Solusia (JURNAL PENDIDIKAN DAN KELUARGA, 2021)
The characteristic of ESP that puts more emphasis on the ability of students to perform tasks relevant to the world of work requires a learning approach that allows the transfer of authentic activities in the work field to the learning activities in the classroom. Many studies then suggest that Task-Based Language Teaching (TBLT) approach meets this special trait. The application of this approach, however, still confuses some ESP teachers or lecturers in which they find it difficult to distinguish the terms of “task” in TBLT with tasks in ordinary classes. This descriptive qualitative research then seeks to describe the nature of tasks in TBLT and reveal the lecturers’ knowledge on that approach. The subjects of the research were all of the lecturers teaching ESP classes at State University of Padang (UNP). The data were obtained through a literature study and interviews. The data gathered then were analyzed qualitatively. The results of the research reveal what task in TBLT is and the extent to which the ESP lecturers know about TBLT